Purchasing Decisions on TikTok Shop among Islamic Boarding School Students: The Roles of Price, Promotion, and Product Quality - Nurul Hidayah; Dwi Setya Nugrahini; Amila Amila (Niqosiya: Journal of Economics and Business Research, 2025)
This study investigates the influence of price, promotion, and product quality on purchasing decisions at TikTok Shop among students of Darussalam Bangunsari Islamic Boarding School, Ponorogo. Using a quantitative approach, data were collected through questionnaires from 104 respondents selected with purposive non-probability sampling. The data were analyzed using multiple linear regression with SPSS 22.0. The results show that price (sig = 0.002 < 0.05), promotion (sig = 0.001 < 0.05), and product quality (sig = 0.000 < 0.05) each have a significant partial effect on purchasing decisions. Simultaneously, these three variables explain 42.1% of the variation in purchasing decisions (R² = 0.421).